2017
DOI: 10.1111/aec.12556
|View full text |Cite
|
Sign up to set email alerts
|

Is the spatial pattern of a tree population in a seasonally dry tropical climate explained by density‐dependent mortality?

Abstract: Spatial pattern of tropical plants is initially generated by limited seed dispersal, but the role of density-dependent and independent mechanisms as modifiers of these patterns across ontogeny is poorly understood. We investigated whether density-dependent mortality (DDM) and environmental heterogeneity can drive spatial pattern across the ontogeny of a tree in a seasonally dry tropical climate. We used Moran's I correlograms and spatial analysis by distance indices (SADIE) to assess the spatial patterns of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
0
3
0
1
Order By: Relevance
“…The study revealed that topographical heterogeneity, which leads to habitat heterogeneity, was the predominant mechanism generating the spatial distribution of most analyzed species [36]. Snags have shown a consistent aggregated distribution at 0-30-m scales in subtropical mountain forests [20].…”
Section: Discussionmentioning
confidence: 90%
“…The study revealed that topographical heterogeneity, which leads to habitat heterogeneity, was the predominant mechanism generating the spatial distribution of most analyzed species [36]. Snags have shown a consistent aggregated distribution at 0-30-m scales in subtropical mountain forests [20].…”
Section: Discussionmentioning
confidence: 90%
“…If there is appreciable temporal variation that affects habitat suitability according to the life stage, which is further modulated by the elevational gradient, then it may have limited our ability to better reconstruct realized patterns via simulation. The dynamics of the juvenile life stages may differ from those of seedlings and adults and may have influenced the overall aggregation (Pereira et al, 2017). Our model was also blind to variation in soil and topographic variables that likely influenced plant vital rates through their effect on moisture and nutriment availability, except to the extent that they may be represented in the elevation contrast.…”
Section: Discussionmentioning
confidence: 99%
“…The fine scale spatial distribution of individuals within plant populations reflects the interplay between deterministic and stochastic processes such as dispersal, local physical conditions and biotic interactions (Antonovics & Levin, 1980;Lara-Romero, Robledo-Arnuncio, García-Fernández, & Iriondo, 2014;Pereira, Martins, Sousa Menezes, & Soares Araújo, 2017;Ripley, 1987;Seidler & Plotkin, 2006). At the same time, it is well-documented that population spatial structure itself may influence the quality and intensity of intra-and interspecific interactions, thereby affecting vital rates and population dynamics (Antonovics & Levin, 1980;North & Ovaskainen, 2007;Seidler & Plotkin, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Los cambios en la vegetación arbórea se dan en función de la dinámica del bosque, que pueden ser expresados por las tasas demográficas de mortalidad, reclutamiento y crecimiento de los árboles (Gross et al 2017). Hay varios factores ecológicos determinantes en este proceso, como aquellos de naturaleza estocástica y determinística, que determinan las características estructurales y espaciales de la vegetación (Silveira et al 2017). El agrupamiento espacial de los individuos muertos y reclutados sugiere, respectivamente, la influencia de factores dependientes de la densidad (por ejemplo, competencia inter e intraespecífica; Larson et al 2016) y de nucleación (por ejemplo, perchas naturales, micrositios favorables a la regeneración; Korndörfer et al 2015).…”
Section: Introductionunclassified